Induction of Tolerogenic Dendritic Cells by Endogenous Biomolecules: An Update - Švajger, Urban; Rožman, Primož (Frontiers in Immunology, 2018)
The importance of microenvironment on dendritic cell (DC) function and development has been strongly established during the last two decades. Although DCs with general tolerogenic characteristics have been isolated and defined as a particular sub-population, it is predominantly their unequivocal biological plasticity, which allows for unparalleled responsiveness to environmental ques and shaping of their tolerogenic characteristics when interacting with tolerance-inducing biomolecules. Dendritic cells carry receptors for a great number of endogenous factors, which, after ligation, can importantly influence the development of their activation state. For this there is ample evidence merely by observation of DC characteristics isolated from various anatomical niches, e.g. the greater immunosuppressive potential of DCs isolated from intestine compared to conventional blood DCs. Endogenous biomolecules present in these environments most likely play a major role as a determinant of their phenotype and function. In this review, we will concisely summarize in what way various, tolerance-inducing endogenous factors influence DC biology, the development of their particular tolerogenic state and their subsequent actions in context of immune response inhibition and induction of regulatory T cells.